1999
DOI: 10.1182/blood.v94.2.600
|View full text |Cite
|
Sign up to set email alerts
|

P-Selectin Expression by Endothelial Cells Is Decreased in Neonatal Rats and Human Premature Infants

Abstract: Decreased adhesion of neutrophils to endothelial cells and delayed transendothelial cell migration of neutrophils have been consistently reported in neonatal animals and humans and contribute to their susceptibility to infection. The delayed transmigration of neutrophils is especially prevalent in premature neonates. To define the nature of this defect, we used an in vivo animal model of inflammation and found that radiolabeled leukocytes from adult rats transmigrated into the peritoneum of other adult rats 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 57 publications
4
17
0
2
Order By: Relevance
“…Developmental differences in E-and P-selectin may underlie the disparities observed in post-ischemic neutrophil infiltration between adult and immature brain. While some studies have shown similar levels of E-and P-selectin in immature and adults rats [92], lower surface expression of P-selectin on endothelial cells or less efficient adhesion of neonatal neutrophils to P-selectin have been described by others [93,94] thus leaving open the question on whether selectins are accountable for the minimal in leukocyte transmigration through the BBB.…”
Section: -3 Adhesion Moleculesmentioning
confidence: 99%
“…Developmental differences in E-and P-selectin may underlie the disparities observed in post-ischemic neutrophil infiltration between adult and immature brain. While some studies have shown similar levels of E-and P-selectin in immature and adults rats [92], lower surface expression of P-selectin on endothelial cells or less efficient adhesion of neonatal neutrophils to P-selectin have been described by others [93,94] thus leaving open the question on whether selectins are accountable for the minimal in leukocyte transmigration through the BBB.…”
Section: -3 Adhesion Moleculesmentioning
confidence: 99%
“…Although the HUC is formed during the fifth week of gestation, the bioenergetic capacity and immune response of HUVEC, obtained from preterm (<37 weeks of gestation) and full-term infants (37-40 weeks of gestation), are different [60][61][62][63][64]. HUVEC, obtained from preterm infants, show an impaired mitochondrial bioenergy capacity, and increased production of reactive oxygen species (ROS) [64].…”
Section: Umbilical Cord Collection and Conservationmentioning
confidence: 99%
“…Illsinger et al demonstrated that HUVEC mitochondrial enzyme activity changes lead to decreased viability of cells obtained from preterm cords [62]. In addition, the expression of selectins is lower in preterm HUVEC as compared to full-term HUVEC [60,61,63]. All these alterations affect endothelial function [60][61][62][63][64].…”
Section: Umbilical Cord Collection and Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…As principais moléculas envolvidas nestas interações são a selectina plaquetária (P-selectina), a selectina endotelial (E-seletina) e a selectina leucocitária (L-selectina) 16 . A P-selectina das plaquetas e células endoteliais é expressa de forma bastante tênue pelo endotélio fetal antes da 27ª semana de gestação, e sua expressão é praticamente normal no recém-nascido a termo e diminuída no recém-nascido pré-termo 22 . A L-selectina é expressa essencialmente nos leucócitos, havendo baixos níveis no cordão de recém-nascidos, principalmente em recém-nascidos pré-termo 23,24 .…”
Section: Fagócitosunclassified